Perbandingan Status Gizi dan Tingkat Dismenorea pada SMPN dan SMP Swasta - Emy Rianti; Fenti Hasnani; Sri Puspita Handayani (Communication and Social Dinamics (CSD), 2022)
Dysmenorrhea is a reproductive system problem that can have an impact on the productivity of young women, including absenteeism from school, decreased concentration in learning, and limitations in carrying out activities. Nutritional status is considered as one of the risk factors for the incidence of dysmenorrhea. The purpose of this study was to compare the relationship between nutritional status and the incidence of dysmenorrhea in adolescent girls in public junior high schools (SMPN) and private junior high schools (SMP). The study design was analytic with a cross sectional approach. Nutritional status was determined based on body mass index according to age (BMI/U). The results showed that there was a difference in nutritional status in SMPN and Private SMP, there was no relationship between nutritional status and the incidence of dysmenorrhea in SMPN. Keywords: nutritional status; dysmenorrhea; adolescent girls ABSTRAK Dismenorea merupakan masalah sistem reproduksi yang dapat berdampak terhadap produktivitas remaja putri, antara lain adalah ketidakhadiran di sekolah, penurunan konsentrasi belajar, serta keterbatasan melakukan aktivitas. Status gizi dianggap sebagai salah satu faktor risiko terhadap kejadian dismenorea. Tujuan penelitian ini adalah membandingkan hubungan status gizi dengan tingkat dismenorea pada remaja putri di Sekolah Menengah Pertama Negeri (SMPN) dan di Sekolah Menengah Pertama (SMP) Swasta. Desain studi bersifat analitik dengan pendekatan cross sectional. Status gizi ditentukan berdasarkan indeks masa tubuh menurut usia (IMT/U). Hasil penelitian didapatkan bahwa ada perbedaan status gizi di SMPN dengan SMP Swasta, tidak ada hubungan antara status gizi dengan kejadian dismenorea di SMPN. Kata kunci: status gizi; dismenorea; remaja putri